Tugas dan Tanggung Jawab Pastry Cook Dalam Pengolahan Panna Cotta di Travello Hotel Bandung - Kartika Dewi; Yeni Fitriani Rahayu (Jurnal Kajian Pariwisata, 2020)
ABSTRACT Hotel is a type of business selling services. A hotel has a department that plays an important role in its operations. One such department is the pastry department. The purpose of this study was to determine the duties and responsibilities of a pastry cook in processing panna cotta in Travello Hotel Bandung, to improve skills in the world of work in the pastry field. In processing the data, the author uses descriptive qualitative research methods. Data collection techniques used in this study is to conduct observations, interviews, documentation, and literature study. The results of this study are duties and responsibilities of the pastry cook at Travello Hotel are good and in accordance with standard operational procedures but further improved communication between staff. Pastry tools are used according to their uses. Pana cotta processing is the same as making pudding, adding gelatine to pana cotta makes the texture of panna cotta soft, panna cotta can be varied with various flavors and toppings. Keyword : Hotel, Panna Cotta, Descriptive